O papel das empresas no desenvolvimento sustentável: a gestão da responsabilidade social corporativa por meio de parcerias sociais - Quilici, Rosangela Bacima (2006)
The subject of this study is the role of the companies in sustainable development: the manage of the corporate social responsibility through the social partnerships. Sustainable development is a big goal of the whole the society. The big challenge is to promote this growth and change with sustainability without damaging the economic, social and environmental conditions. But the current scenario in these three dimensions is worrying, featuring a sustainability crisis in which the representative sectors of society take part: governments, private organizations and civil society and over which everybody has responsibility of action. In the companies the co-responsibility ethics and the participation posture in public interest issues gave origin to the corporate social responsibility, understood as an indicator of their legitimacy and relevance in their segment and regions of act. In this view, corporate social responsibility is a business development corporate strategy associated with the development of the communities where the company acts, within the concept that there are no strong companies in needy societies and in societies with no conditions to consume. The more, the practice of corporate social responsibility is linked to public policies, to guarantee scale and wide-ranging action, the stronger its contribution to the sustainable development and its return on private social investment will be. Concrete results will be more significant provided that global initiatives exist among the three sectors of society, on an integrated action of shared responsibility and partnership. Social partnership is a privileged alternative to the corporate social investment management, by articulating views, competences and resources, focusing on global acts towards public interest issues and on reaching results which are relative to the problem to be solved and the work to be done. The objective of this work is to study the practice of social partnerships as effective strategies for companies, governments and social civil organizations which are willing to work together and to build cultural change and new interactive and complementary dynamics among them, cooperating towards the positive transformation of the sustainable development indicators